Fabrication of MEA with hydrocarbon based membranes using low temperature decal method for DMFC - Krishnan, N. N.; Prabhuram, J.; Hong, Y. T.; Kim, H. -J.; Yoon, K.; Ha, H. -Y.; Lim, T-H.; Kim, S. -K. (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
The membrane electrode assembly (MEA) with hydrocarbon (HC) based membranes made by a low temperature decal method has been investigated for the direct methanol fuel cells (DMFCs). The conventional low temperature decal (LTD) transfer method (comprised of three layers; viz., carbon, Nafion bonded electrodes and outer ionomer layers over the decal Teflon substrates) meant for the MEAs made of Nafion type membranes is suitably modified to use with hydrocarbon (HC) based membranes. The modification of conventional LTD method is effected by means of modulating the three-layered structure and optimizing other parameters to facilitate complete transfer of catalyst layers onto the HC membranes. The MEAs prepared by the modified LTD method have yielded 21 % higher DMFC performance compared to that of the MEAs produced by conventional LTD method. The structure and electrochemical properties of the MEAs have been analyzed by the field-emission scanning electron microscopy (FE-SEM) and the electrochemical impedance spectroscopy (EIS). (C) 2010 Professor T. Nejat Veziroglu. Published by Elsevier Ltd. All rights reserved.
Keywords: METHANOL FUEL-CELL; ELECTROLYTE MEMBRANE; PERFORMANCE; BLENDS; POLYBENZIMIDAZOLE; DESIGN